Pengaruh Motivasi Kerja dan Lingkungan kerja terhadap Produktivitas Kerja Petani Gula Aren Oemah Semut Desa Pedawa Kabupaten Buleleng - Darmendra, I Made Risci; Suci, Ni Made (Universitas Pendidikan Ganesha, 2022)
This study aims to examine the effect of work motivation and work environment on the work productivity of palm sugar farmer Oemah Semut, Pedawa Village, Buleleng Regency. The research design in this study is causal quantitative. The object of research is work motivation, work environment and work productivity. The population in this study were members of the palm sugar farmer group, Oemah Semut, Pedawa Village, Buleleng Regency, amounting to 37 people. Data was collected by using a questionnaire technique which was analyzed using path analysis. The results showed that, (1) work motivation had a positive and significant effect on work productivity, (2) the work environment had a positive and significant effect on work productivity, (3) motivation had a positive and significant effect on the work productivity of palm sugar farmers Oemah Semut Pedawa Village, District Buleleng through the work environment, (4) motivation and work environment have a positive and significant effect on the work productivity of palm sugar farmer Oemah Semut, Pedawa Village, Buleleng Regency.